5G mobile communications : concepts and technologies - Asif, Saad Z. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2018)
This book will describe the next evolution of mobile wireless communications, Fifth Generation and will be explained both from network and device perspective. Chapters and sections will be dedicated to illustrate the key stages involved in the development of new generation, 5G including research and technology development, standardization, component, semiconductor and product development, network development, and device and application development. Examples and case studies will be provided throughout the text--
The beginning -- Research & technology development -- Radio frequency spectrum -- Standardization -- 5G concepts -- Semiconductor in mobile telecommunications -- Product development -- Network architecture, mobility management & deployment -- 4G/5G radio access network -- Transport network -- Core network & operational support system -- Connected devices -- Mobile applications -- Burning challenges -- Weak, good, and best industry practices -- Way forward.
'A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc.'
Includes bibliographical references and index.
Keywords: Mobile communication systems -- Technological innovations; Wireless communication systems -- Standards